Controlling the Graphene-Bio Interface Dispersions in Animal Sera for Enhanced Stability and Reduced Toxicity - Pattammattel, Ajith (Langmuir : the ACS journal of surfaces and colloids, 2017)
Liquid phase exfoliation of graphite in six different animal sera and evaluation of its toxicity are reported here. Previously, we reported the exfoliation of graphene using proteins, and here we extend this approach to complex animal fluids. A kitchen blender with a high-turbulence flow gave high quality and maximum exfoliation efficiency in all sera tested, when compared to the values found with shear and ultrasonication methods. Raman spectra and electron microscopy confirmed the formation of three- or four-layer, submicrometer size graphene, independent of the serum used. Graphene prepared in serum was directly transferred to cell culture media without post-treatments. Contrary to many reports, a nanotoxicity study of this graphene fully dispersed to human embryonic kidney cells, human lung cancer cells, and nematodes (Caenorhabditis elegans) showed no acute toxicity for up to 7 days at various doses (50-500 μg/mL), but prolonged exposure at higher doses (300-500 μg/mL, 10-15 days) showed cytotoxicity to cells (∼95% death) and reproductive toxicity to C. elegans (5-10% reduction in brood size). The origin of toxicity was found to be due to the highly fragmented smaller graphene sheets (<200 nm), while the larger sheets were nontoxic (50-300 μg/mL dose). In contrast, graphene produced with sodium cholate as the mediator has been found to be cytotoxic to these cells at these dosages. We demonstrated the toxicity of liquid phase exfoliated graphene is attributed to highly fragmented fractions or nonbiocompatible exfoliating agents. Thus, low-toxicity graphene/serum suspensions are produced by a facile method in biological media, and this approach may accelerate the much-anticipated development of graphene for biological applications